National Academies Board on Human-Systems Integration (BOHSI) Panel: Exploring the Changing Nature of Work. (September 2021) - Oswald, Fred; Imada, Andrew S.; Behrend, Tara; Endsley, Mica R.; Hancock, Peter; Oswald, Fred; Spence, Deborah; Weinger, Matthew R.; Warden, Toby
The National Academies Board on Human Systems Integration (BOHSI) has organized this session exploring the changing nature of an essential human activity—work. Policing, the military, healthcare, and numerous other fields are being shaped by powerful forces. The Panel brings together prominent researchers to reflect on the organizational and societal changes as well as the impact of emerging technologies that are likely to shape the nature of work in the future.